Penggunaan Dua Media Daring dalam Pembelajaran Bahasa Jepang Dasar pada Masa Pandemi Covid-19 - Nita Rustanti (Universitas Gadjah Mada, 2022)
The purpose of this research was to increase student’s speaking skills of Basic Japanese for nurse using two online media during the pandemic Covid-19 period. The learning process was carried out online using e-learning and google meet. This research was conducted on 40 students from nursing major at Bhakti Kencana University, Bandung from October 2021 until January 2022. This research used action researched method with two cycles. Data were obtained through observation and questionnaires. The results showed that there has been increased student’s speaking skill, students could understand the material more quickly, and students were more independent because the material can be accessed anywhere. The obstacles in the learning process of basic Japanese are the signals were often unstable during the teaching and learning process, the environment was too noisy, and there were errors in the e-learning system.